The (after) life-cycle theory of religious contributions - S. Brock Blomberg; Thomas DeLeire; Gregory D. Hess (Center for Economic Studies and ifo Institute (CESifo), 2006)
We construct and estimate an economic model of religious giving. We employ a dynamic consumer optimization model with mortality in which intra-temporal utility stems from both consumption and religious contributions. Individuals also decide how to allocate resources between religious contributions (which have both a this-life consumption value and an afterlife investment value) and other consumption expenditures. If religious contributions do not have an after-life investment value, the ratio of contributions to consumption expenditures should be unrelated to the probability of death. However, if there is an investment value from religious giving, individuals should allocate a greater share of their income to religious contributions as their probability of death increases. We estimate the model using data from the Consumer Expenditure Survey on the consumption and religious contribution patterns of a repeated cross-section of households and of a synthetic cohort panel. We find strong evidence that individuals behave as if religious contributions have a value in the after-life, in a manner consistent with the after life-cycle model. The estimates of the structural parameters of the model also imply that while after-life investment considerations (i.e. impending death) are an important determinant of the life-cycle profile of religious contributions, within-life (i.e. religious consumption) factors pin down a household's average level of religious contributions over a lifetime.
Keywords: H1; H5; H8; 330